Canela - Miles, Ellen (New York : Scholastic, Inc., 2006)
Charles and Lizzie Peterson love puppies. They want a puppy of their own more than just about anything. They know dogs are a lot of work. But their Mom still doesn't think their family is ready for a puppy. Then, Goldie arrives. She is a sweet golden retriever who needs a home. Goldie is very young. She doesn't know how to be a good puppy yet. Will Charles and Lizzie be able to help her?
Translation of: Goldie.
"Cachorritos, todos los perritos necesitan un hogar"--cover.
"First Spanish printing, October 2006"--T.p. verso.
Keywords: Golden retriever -- Juvenile fiction; Dogs -- Juvenile fiction; Puppies -- Juvenile fiction; Spanish language materials